Compensating displaced workers - Donald O. Parsons (IZA World of Labor, 2024)
Job displacement is a serious earnings risk to long-tenured workers, both through spells of unemployment and through reduced wages on subsequent jobs. Less developed countries often rely exclusively on government mandated employer-provided severance pay to protect displaced workers. Higher income countries usually rely on public unemployment insurance and mandated severance pay. Beyond these options, more administratively demanding plans have been proposed, including UI savings accounts and "actual loss" wage insurance, though real-world experience on either model is lacking.
Keywords: 330; job displacement; unemployment insurance; severance pay; wage insurance; UI savings accounts